Effects of Early and Delayed Antiretroviral Therapy on Plasma Anti-CD4 Autoreactive IgG and Its Association With CD4+ T-Cell Recovery in Acute HIV-Infected Individuals - Song, Aixin; Li, Zhen; Luo, Zhenwu; Lu, Xiaofan; Wang, Rui; Liu, Lifeng; Xia, Wei; Wan, Zhuang; Zhang, Tong; Su, Bin; Jiang, Wei; Wu, Hao (Frontiers in Pharmacology, 2020)
Background Plasma levels of anti-CD4 autoantibodies are increased in chronically HIV-infected patients and inversely correlated with CD4+ T-cell recovery under viral-suppressive antiretroviral therapy (ART). However, it remains unknown the effect of early ART on plasma anti-CD4 autoantibody levels in acute HIV infection (AHI). Methods In this cohort study, we evaluated the effect of early and delayed initiation of ART on plasma anti-CD4 autoantibody levels in AHI individuals (n = 90). Blood samples were collected from men who had sex with men (MSM) with acute infection, pre-ART, and 4, 24, 48, and 96 weeks after ART. Plasma levels of anti-CD4 immunoglobulin G (IgG) were measured by ELISA. Results We found that plasma anti-CD4 IgG levels were significantly increased in AHI individuals compared with healthy controls (HCs) prior to ART. Notably, early ART decreased plasma anti-CD4 IgG to the levels similar to HCs starting at 24 weeks (W). However, delayed initiation of ART did not significantly reduce plasma anti-CD4 IgG levels in AHI individuals. Moreover, the peripheral CD4+ T-cell counts were inversely correlated with plasma anti-CD4 IgG levels in AHI individuals at 48 and 96 W after early ART but not after delayed ART. Conclusions Taken together, our findings demonstrate for the first time that early ART, but not delayed initiation of ART, is effective in influencing anti-CD4 autoantibody production and recovering CD4+ T-cell counts in AHI individuals.